2013
DOI: 10.20419/2013.22.374
|View full text |Cite
|
Sign up to set email alerts
|

Working status and perception of adulthood: a comparison between Italian and Dutch emerging adults

Abstract: Abstract:The purpose of this study was (a) to identify the criteria Italian and Dutch emerging adults consider important to achieve adulthood; (b) to compare Italian emerging adults' criteria with the criteria espoused by Dutch emerging adults; and (c) to examine how these criteria might differ on the basis of the working status (temporary job contract vs. permanent job contract) of the participants. Participants included 111 Italian (M age = 25) and 151 Dutch (M age = 22) university working students. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…Correlations among subscales regarding criteria for adulthood were small to moderate in magnitude (ranging from r = .20, p < .01 to r = .60, p < .01) confirming that these domains in which adult status is expected to be demonstrated, reflect different facets or markers of adulthood. Similar results were obtained in previous studies (e.g., Piumatti et al, 2013; Petrogiannis, 2011). The correlation between life satisfaction and education satisfaction was equal to .22, p < .01, confirming that these constructs were describing different facets of satisfaction.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Correlations among subscales regarding criteria for adulthood were small to moderate in magnitude (ranging from r = .20, p < .01 to r = .60, p < .01) confirming that these domains in which adult status is expected to be demonstrated, reflect different facets or markers of adulthood. Similar results were obtained in previous studies (e.g., Piumatti et al, 2013; Petrogiannis, 2011). The correlation between life satisfaction and education satisfaction was equal to .22, p < .01, confirming that these constructs were describing different facets of satisfaction.…”
Section: Resultssupporting
confidence: 93%
“…Thus, following the theory of emerging adulthood, positively adjusted emerging adults are in the process of becoming less self-oriented and ready to commit themselves to enduring relationships with others by showing a predisposition to be involved in relations and maintaining a strong focus on their actions and goals (e.g., Arnett, 2003; Isaacs, Soglian, & Hoffman, 2015; Nelson & Padilla-Walker, 2013). The transition towards the endorsement of other-related criteria for adulthood would take place with ageing, earlier for females than for males, and with the increasing experiencing of independent living conditions, a certain degree of economic self-subsistence and long term relationships (e.g., Cheah, Trinder, & Gokavi, 2010; Kins & Beyers, 2010; Lanz & Tagliabue, 2007; Nelson & Barry, 2005; Piumatti, Giannotta, Roggero, & Rabaglietti, 2013). Concurrently, mainly transition-linked increases (e.g., leaving the parental home, finishing education, getting a job) may contribute to the endorsement of certain criteria (e.g., family responsibilities when getting married, interdependence when starting a new relationship, independence when getting a job) and accompany increases in psychological well-being such as positive life-satisfaction (Galambos, Barker, & Krahn, 2006; Galambos & Krahn, 2008; Kins & Beyers, 2010).…”
Section: Criteria For Adulthoodmentioning
confidence: 99%
“…In the past, a majority of young adults would have married by their mid‐20s and formed families (Furstenberg Jr. ; Surra et al ). However, over the past few decades, a statistical shift has been developing, as more and more young adults have postponed these and other life goals, often until their late 20s or their 30s (Eliason, Mortimer, and Vuolo ; Piumatti et al ). In the United States, many young adults continue to rely on parents well into their third decade of life, not only for emotional but also for financial support (Fingerman et al ).…”
mentioning
confidence: 99%
“…In Canada, final year high school students (18-year-olds) expressed concern about the effects of the growing level of precarious employment on their education, believing that they needed to put more effort into their schooling in order to secure satisfying work (Lowe & Krahn, 2000). On the other hand, Piumatti et al (2013) found no differences between working students (Dutch and Italian) who had temporary job contracts (i.e., the precarious group) and those with permanent jobs on measures of criteria for adulthood (e.g., perceived capacity to purchase a house when an adult). In the United States, Kim et al (2009) found that, for university students working in the retail sector, more negative perceptions of job characteristics were related directly to less job satisfaction and work involvement and related indirectly (via lower job satisfaction) to a reduced intention to seek a career in retail, indicating that precarious employment was related to work attitudes, current functioning, and future work plans.…”
Section: Precarious Employmentmentioning
confidence: 99%